Analisis Pengaruh Brand Image dan Brand Trust Terhadap Keputusan Pembelian Sepatu Nike - Sutanto, Farrel Yustinus; Agustini, M.Y. Dwi Hayu (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Nike is a leading sports shoe brand that very popular and in high demand in Indonesia. However, Nike ranks second among the top five footwear brands in the country. This study aims to investigate how brand image affects the act of buying Nike shoes and to evaluate the role of brand trust in moderating the relationship between brand image and purchase decision. This study was conducted on Nike shoe wearers in Semarang City. The sample for this study was selected using snowball sampling, starting from friends and acquaintances who also wear Nike shoes. Questionnaires were used to collect data, and partial least squares structural equation modelling (PLS-SEM) was used to analyse the results. The results show that brand image, through brand trust, has a positive and significant effect on purchasing decisions. Nike footwear manufacturers need to use various marketing techniques to increase customer trust and strengthen Nike's brand identity through information transparency and consumer engagement.